'All-under-Heaven' (tianxia 天下): between idealism and realism. Issue 1 (2nd January 2021) - Zhao 赵汀阳, Tingyang
ABSTRACT: As an idealist form of realism, or realist form of idealism, the system of 'All-under-Heaven' ( tianxia 天下) seeks to find a rational and optimal solution to the problem of political conflict. However, it does not purport to offer the promise of universal happiness for all. Rather, this system envisages the possibility of another world; one of peace, general security, and civilizational vigor. In this sense, it is radically different from various proclamations of 'the end of history'. The following aspects of the notion of tianxia are particularly worth emphasizing: firstly, 'All-under-Heaven' is not a utopia at all, but rather an ideal that can actually be realized. Secondly, the goal of a politics of tianxia is to resolve the problem of conflict by transforming hostility into hospitality, thus offering a new conception of politics beyond the struggle for power. Thirdly, the vision of 'All-under-Heaven' is grounded in three constitutive concepts, namely the 'internalization of the world', relational rationality, and 'Confucian Improvement', which together constitute a politics capable of transforming hostility into hospitality.